Husband Abuse: Equality with a Vengeance? - Minaker, Joanne Cheryl (Canadian journal of criminology and criminal justice, 2006)
The original problem of 'wife abuse,' which feminists constituted in the 1970s, has morphed into 'domestic violence' and then into 'husband abuse.' We present a case study of the newly discovered problem of 'husband abuse,' which we argue exemplifies the complexities of neo-liberalism, neo-conservatism, and feminist engagement with the criminal-justice state. We argue that the myth that men are battered as often as women, an argument that challenges decades of feminist research, theory, and activism, is constitutive of a backlash against women's safety and feminist 'victories.' We caution that such claims must be read as more than anti-feminist backlash but are increasingly becoming the new 'common sense,' the dominant lens used by policy makers, media, and influential interest groups. We demonstrate how the very successes of feminism, combined with neo-liberal governance, the burgeoning power of men's movements, and new communication media, have given rise to new subjects, mentalities, and practices. As the claim that male and female partners are equally prone to violence resonates with discourses of equality and reinforces constituencies promoting criminal-justice 'solutions' to all social problems, the result is equality with a vengeance. (English) [ABSTRACT FROM AUTHOR]